PENGARUH MACAM PUPUK KANDANG PENGARUH UMUR PANEN TERHADAP HASIL TANAMAN KANGKUNG DARAT (Ipomoea reptans) Var. Bangkok LP-1 DI LAHAN PASCA ERUPSI MERAPI - Ginanjar Tri Wahono; Murti Astiningrum; Yulia Eko Susilowati (JURNAL VIGOR, 2018)
The research of effort to increase the yield of kale (Ipomoea reptans) was conducted on 01 August 2016 until 06 November 2016. The field experiment was on land of post eruption of Mount Merapi in Sawangan Village, Sawangan District, Magelang Regency. The altitude is 485 m, The soil isregosol with pH 5,5. The research used factorial experiment. One factor treatment of age of harvesting 17, 20, 23, 26, 29, 30, and 32 days after planting arranged in randomized complete block design replicated four times. The results show that the treatments of days of harvesting high significantly influence all observed parameters. Increasing number of days of harvesting may increase parameters observed. The highest yield of edible parts is on 27th days of harvesting.